THE MEDIATING ROLE OF E-WOM IN THE EFFECT OF ONLINE EVENT EXPERIENCE ON EVENT REPARTICIPATION: MULTIGROUP ANALYSIS IN STRUCTURAL EQUATION MODELING (Third Sector Social Economic Review, 2024)
Physical contact, which decreased with the Covid-19 pandemic, has expanded the fields of activity of online environments and enabled consumers to have experiences in these environments.This study focuses on the experience of consumers in online events. It examines the direct and indirect relationships between online event experience, e-WoM and intention to reparticipation, and whether these relationships differ according to the type of event. The data obtained from the participants of the online events and the relationships in the research model were analyzed using SmartPLS program, and the direct and indirect effects were examined by structural equation modeling and whether these relationships differed according to the type of event was examined by multigroup analysis. When the results obtained are evaluated, it is observed that although it varies according to the types of events, in general, online event experience has an effect on e-WoM and reparticipation, and e-WoM has an effect on event reparticipation. In addition, the mediating role of e-WoM in the relationship between online event experience and event reparticipation was determined. According to the results of multigroup analysis, it was found that there was a difference in the effect of online event experience on e-WoM and event reparticipation according to the type of event, but the type of event did not make a difference in the effect of e-WoM on event reparticipation.
Keywords: Online events; event experience; reparticipation; e-WoM; Multigroup analysis